Occupational hazard in Malaysian traffic police: special focus on air pollutants - Mohamad Jamil, Putri Anis Syahira; Karuppiah, Karmegam; Rasdi, Irniza; How, Vivien; Mohd Tamrin, Shamsul Bahri; K. C. Mani, Kulanthayan; Sambasivam, Sivasankar; Sadeghi Naeini, Hassan; Mohammad Yusof, Nur Athirah Diyana; Hashim, Nurul Maizura (Walter de Gruyter GmbH, 2021)
This paper provides a specific deliberation on occupational hazards confronted daily by Malaysian Traffic Police. Traffic police is a high-risk occupation that involves a wide range of tasks and, indirectly, faced with an equally wide variety of hazards at work namely, physical, biological, psychosocial, chemical, and ergonomic hazards. Thereupon, occupational injuries, diseases, and even death are common in the field. The objective of this paper is to collate and explain the major hazards of working as Malaysian traffic police especially in Point Duty Unit, their health effects, and control measures. There are many ways in which these hazards can be minimised by ensuring that sufficient safety measures are taken such as a wireless outdoor individual exposure indicator system for the traffic police. By having this system, air monitoring among traffic police may potentially be easier and accurate. Other methods of mitigating these unfortunate events are incorporated and addressed in this paper according to the duty and needs of traffic police.